476 Training basic researchers in translational approaches to facilitate the application of laboratory discoveries. (April 2022) - Dillon, Pamela; Lloyd, Joyce; Sarkar, Devanand
Abstract : OBJECTIVES/GOALS: To maximize health outcomes from their work, basic researchers must understand the process by which lab discoveries are translated into clinical care. We developed an academic course designed to provide students in our Clinical and Translational Sciences PhD program with an in-depth understanding of translational applications of basic research. METHODS/STUDY POPULATION: A preliminary needs assessment was done with students, educators, and clinicians to identify the course content. Based on these data, didactic modules including research question identification, research team development, participant recruitment, and research data collection were piloted in a synchronous, virtual course. Then, for 6 weeks, students shadowed clinical mentors who worked in the students research areas. Finally, with their mentors, students developed and presented clinical research protocols. Student pre- and post-course surveys gauged alignment of course objectives and learning outcomes. A post-course, focus group with students gathered feedback on course content, structure, and students confidence in implementing their experiences from the course into real-world settings. RESULTS/ANTICIPATED RESULTS: Six MD/PhD and PhD students participated in the pilot course. Pre/post-assessments (n=4) showed students were more confident in clinical question/research protocol formulation, development of patient recruitment/enrollment strategies, and integration of research methodologies into their research projects after completing the course. Students asked for additional content on budgeting and grant funding. Post-course focus group participants (n=2) appreciated the experience of writing a clinical protocol and the flipped classroom teaching style, which allowed them to network with clinical faculty leading didactic sessions. Students also noted course content was relevant and motivating, although they suggested adding content about clinical trials measures to enhance their shadowing experiences. DISCUSSION/SIGNIFICANCE: A course that combines didactic and clinical experiential training provides a robust, translational research foundation for basic scientists. This training is critical to help them contribute to the effective/efficient translation of lab discoveries to clinical practice. Future course development will include students from other PhD programs.